PSII-15 Hydrogenation of palm kernel oil, palm oil, and soybean oil on energy and lipid digestibility, and performance when fed to 20 to 40 kg pigs. (30th November 2020) - Breuer, Sophia; Kerr, Brian
Abstract: The objective of this study was to evaluate the effect of feeding hydrogenated palm kernel oil (PKO), palm oil (PO), or soybean oil (SO) relative to unhydrogenated PKO, PO, and SO on apparent total tract digestibility (ATTD) of gross energy (GE) and ether extract (EE), and on pig performance, in to 20 to 40 kg pigs. One hundred and fifty-four pigs (39.5 ± 3.6 kg BW) were randomly assigned to one of 9 diets composed of a basal diet, or test diets containing 94% of the basal diet and 6% added lipid. Lipids consisted of either unhydrogenated or hydrogenated PKO, PO, or SO in a factorial arrangement. The basal diet contained titanium dioxide as an inert maker and was used to determine the ATTD of GE or EE of each lipid using the difference method. There were 2 pigs per pen with pigs ad libitum fed for 25 d to measure growth performance. On d 23 and 24, a fresh fecal sample was obtained from each pen to measure ATTD of GE and EE. There was an interaction between lipid source and hydrogenation for ATTD of GE and EE of the lipid (P ≤ 0.01), where hydrogenation of PKO had no effect on ATTD of GE or EE of the lipid, while hydrogenation of PO and SO resulted in a reduction in the ATTD of GE and EE compared to their unhydrogenated counterparts. There was also an interaction between lipid source and hydrogenation on GF (P ≤ 0.01) where hydrogenation of PKO had no effect on GF while hydrogenation of PO and SO resulted in a reduction in GF compared to their unhydrogenated counterparts. The data show that hydrogenation of PKO has no impact on ATTD of GE and EE of the lipid, or on GF, but hydrogenation of PO or SO reduce ATTD of GE and EE of the lipid, and GF, due to their fatty acids being longer in carbon chain length.